PENGUKURAN PERCEPATAN GRAVITASI BUMI MENGGUNAKAN AYUNAN MATEMATIS BERBANTUAN ALS (AMBIENT LIGHT SENSOR) PADA SMARTPHONE ANDROID (UPEJ Unnes Physics Education Journal, 2023)
The acceleration experienced by an object as a result of the influence of the earth's gravitational field, which is directed towards the center of the earth, is referred to as gravitational acceleration. The use of mathematical pendulum is one method for measuring the acceleration of Earth's gravity. Analyzing the period of swing experienced by the pendulum allows for the calculation of gravity's acceleration using mathematical pendulum. When the pendulum is swung, a light sensor (Ambient Light Sensor) on an android smartphone is used to read the intensity of the ambient light. The Arduino Science Journals application is used to obtain the value of the light intensity sensor on the smartphone. The light intensity value obtained is used to obtain the swing period after being analyzed using a spreadsheet application. In this experiment, two smartphones, the Samsung Galaxy A50 and the Vivo Y12, were used as a comparison in the data collection process, as well as a height-adjustable stand, a pendulum, a rope, and tools in the form of a meter and a tripod. The acceleration of gravity measured at the site of the research was obtained by using the Samsung Galaxy A50 with a relative error of and by using the Vivo Y12 with a relative error of .